Financial Distress Analysis Using the Altman Z-Score Model in the Household Equipment Sub-Sector Listed on the Indonesian Stock Exchange - Inta Budi Setya Nusa; Deni Solihin; Boyke Nugrahanto (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This research aim is to analyze financial distress using the Altman Z-Score model which is seen as a method used to predict company’s sustainability by combining several financial ratios in household equipment sub-sector listed on the Indonesia Stock Exchange(IDX) from 2018 to 2022. Qualitative approach is used in this research with descriptive analysis method to solve the problem. Secondary data used in this research is in the form of historical reports from companies that have been created, compiled and published. Secondary data collection used includes company financial report data. The data analysis technique uses the first Altman Z-Score Model (AZM). The research results show that an average Z-Score value of 2.03, means that the company is in a bankruptcy-prone condition or gray area.